The Role of Islamic Religious Education for the Character of Youth in Association - Arli Marlina; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Islamic religious education is very important for character building, especially in socializing the community. In today's era students tend to not care about society, therefore forming a good character is very important, especially in social society. Islamic religious education itself teaches that we are required to have good character according to what was taught by the Prophet Muhammad SAW; Allah SWT says, which means